FATORES ASSOCIADOS À INFECÇÃO POR LEISHMANIA CHAGASI EM INDIVÍDUOS ASSINTOMÁTICOS NO MUNICÍPIO DE RAPOSA - MA - Cavalcante, Maria Neusa Sousa (2009)
Visceral Leishmaniasis is a zoonosis that attacks man in an accidental way and in the present decade presents itself in a wide geographic expansion, attacking urban and peri-urban spaces of large Brazilian cities. The precarious social/economic and environmental conditions, as well as life habits are relevant to the epidemiology of the disease and seem to favor the maintaining of the transmission cycle. A Cohort study was accomplished during the period of August 2006 to January 2008, with the objective of investigating the occurrence of non-symptomatic infection by Leishmania chagas in humans in the villages of Maresia, Pantoja and Marisol in the municipal area of Raposa, MA. The study was delineated in three phases: in the first phase, a population census was taken; in the second phase, demographic, social/economic and epidemiologic data was collected using a questionnaire, as well as a physical examination and tests to detect the infection by Leishmania chagasi in 1371 individuals by the immune enzymatic test (ELISA), and in 1356 individuals by the Montenegro skin test (IDRM); and in the third phase, the physical exam as well as the ELISA test was performed on 958 individuals. In the statistical analysis of the risk factors, a logistic regression and Poisson test in the Stata 9.0 program was used, having a significant level p<0,05 (95%). The initial and final prevalence and the incidence of infection by Leishmania chagasi by means of the ELISA test was 19,8%, 16,6% and 8,4% respectively, and the prevalence by means of the IDRM test was 82%. The following variables were found to be associated with the incidence of infection by Leishmania chagasi by the ELISA test: over 15 years of age (p<0,001) and the presence of more than 4 dwellers in a residence (p=0,039); and association with the prevalence of infection by Leishmania chagasi by the IDRM test were: over 15 years of age (p=0,003), straw or adobe walls (p=0,0014), a poultry-gard present (p=0,004) and reference to mosquito-breeders in the peridomiciliar (p=0,026). The high prevalence detected by the IDRM in the localities studied indicates a large exposure of the dwellers to the vetor of LV, and the incidence detected by the ELISA demonstrates the vulnerability of the individuals to the risk of contracting the disease.